BRAIN DRAIN AND ITS REPERCUSSIONS ON THE NEEDS OF THE PALESTINIAN LABOR MARKET: A STUDY OF THE CAUSES AND CONSEQUENCES OF MIGRATION AMONG EDUCATED YOUTH - Hamarsha, Manal Mohammad (Applied Studies in Agribusiness and Commerce, 2025)
This study examines the consequences of the outflow of young people from the occupied territories for the Palestinian labor market. This phenomenon is labeled a "drain" because it deprives the area of many educated individuals needed for its development. Commonly discussed as a political issue and as a consequence of war, the problem is often not addressed as an economic issue. Moreover, emigration exacerbates the population problem as young females and males leave the area for neighboring states and seek permanent sanctuary in them. When this group is not present to aid in the process of internal development, the investment in their education is lost. In all areas of the world, one may observe graduations from universities and other institutions leading to the majority of proficient students leaving or attempting to leave to assume responsible positions. This exodus constitutes a serious problem for the donor country in the sense of its youth development, and a serious problem for the recipient country deprived of the services of these skilled graduates. The total "drain" of the talented becomes an important economic problem. The outflow of trained individuals is not unique to Palestine; therefore, similar serious situations are prevalent in many developing countries, particularly those situated in proximity to concentrations of wealth. The magnitude of the Palestinian outflow, however, has not previously been demonstrated. The analysis of Palestine’s probable situation was accepted reluctantly, as many information sources refused or were too cautious to share statistics related to this study. The specific objective of the analysis is to present these and related statistics. The concern in this paper is with the consequences of the phenomenon and the associated costs in disutility. There are other consequences and costs, all of which are important.